Children and their education in secure accommodation: interdisciplinary perspectives of education, health and youth justice - Gallard, Diahann; Evans, Katharine; Millington, James (Routledge, Taylor & Francis Group, 2019)
Troubled and troublesome children : education, participation and restoration / Ben Byrne -- A historical perspective on education in secure accommodation in England and Wales from 1850 to the present / Caroline Lanskey -- Specialist education provision within secure CAMHS units / Faiza Ahmed -- Roles and relationships of care and education staff inside a secure children's home / Caroline Andow -- How psychological services and education link up in secure children's homes / Alex Smith and Sarah Mack -- Children's lives, education and secure care in Scotland / Alison Gough and Claire Lightowler -- Behind the headlines, inside the walls, teaching Britain's hidden children : perspectives and practices within the Secure Children's Homes Network / Melanie Prince, Aileen Conlon, Marc Herbert, Phillippa Brooks and Sarah Douglas -- A secure children's home in Wales : care and educational provision from clinical, management and educational perspectives / Richard Pates, Alison Davies and David Tiddy -- Aligning with the chaos and navigating through the trauma / Deirdre McConnell, Kate Brown, Yanela Garcia and James Stephens -- The nature-based residential treatment centre as an alternative model for meeting the needs of children and young people / Steven Klee, Joanna L. Becker and Miyako Kinoshita -- Youth voice and participation in secure settings for young people / Caroline Lanskey -- Children's views of education in a young offenders institution / Ross Little -- Safeguarding children in the youth justice secure estate / Katharine Evans -- Identifying barriers and facilitators for educational inclusion for young people who offend : practitioner and youth perspectives / Jenny Twells -- Re-engaging young offenders with education in the secure custodial setting / Adeela ahmed Shafi -- The banter levels are good : developing social and human capital through education / Anita Mehay and Nina Champion -- Where are we going? : context and directions for policy and practice in children's education in secure accommodation / Ross Little